Aggressive, early resistant and relapsed mantle cell lymphoma distinct extrinsic microenvironment highlighted by transcriptome analysis. Issue 4 (13th October 2022) - Le Bris, Yannick; Normand, Adeline; Bouard, Louise; Ménard, Audrey; Bossard, Céline; Moreau, Anne; Béné, Marie C.
Abstract: Immunotherapy strategies relying on innate or adaptive immune components are increasingly used in onco‐haematology. However, little is known about the infiltrated lymph nodes (LN) or bone marrow (BM) landscape of mantle cell lymphoma (MCL). The original transcriptomic approach of reverse transcriptase multiplex ligation‐dependent probe amplification (RT‐MLPA) was applied here to explore the expression of 24 genes of interest in MCL at diagnosis (21 LN and 15 BM) or relapse (18 LN). This allowed us to identify that at baseline, samples from MCL patients with an aggressive morphology (i.e. blastoid or pleomorphic) or a high proliferative profile, displayed significantly higher monocyte/macrophage‐associated transcripts ( CD14 and CD163) in LN and BM. Regarding T‐cells, aggressive MCL forms had significantly lower amounts of LN CD3E transcripts, yet an increased expression of cytotoxic markers in LN ( CD8 ) and BM ( CD94 ). A very high‐risk group with early treatment resistance displayed, at diagnosis, high proliferation ( KI67 ) and high macrophages and cytotoxic transcript levels. Post‐immunochemotherapy relapsed samples revealed lower levels of T‐ and natural killer‐cells markers, while monocyte/macrophage markers remained similar to diagnosis. This study suggests that rapid analysis of MCL microenvironment transcriptome signatures by RT‐MLPA could allow for an early distinction of patient subgroups candidates for adapted treatment strategies.